Españolas exiliadas y emigrantes : encuentros y desencuentros en Francia - Alicia Mira Abad; Mónica Moreno Seco (Les Cahiers de Framespa)
The Spanish colony in France changed during the twentieth century. Each successive wave of Spanish men and women presented new characteristics: sometimes this made life together difficult, but there were also many similarities, which were made stronger by daily interactions. Political militancy, social class and cultural activities were categories which crossed over and created a variety of situations. Another such category was gender: if we ignore women’s experiences, we then fail to appreciate many aspects of the rivalry between migrants and exiles, or of the forms of integration into the host country. Migrant and exiled women found meeting-spaces, and created networks of solidarity among themselves: these were more frequent and stronger than those created by men, although one must not forget that tension and conflicts still existed within these groups which, has been discussed elsewhere, shared geographic locations and modest socio-economic positions. These links developed most strongly in the areas in which significant numbers of Spaniards lived, such as the south-west of France, the Parisian region and Algeria.